Delivering Singlet Oxygen in Dark Condition With an Anthracene-Functionalized Semiconducting Compound for Enhanced Phototheranostics - Shen, Jian; Pan, Liuhong; Zhang, Xujing; Zou, Zhenyuan; Wei, Bo; Chen, Yongchang; Tang, Xiaoyan; Zou, Dengfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Photodynamic therapy (PDT) utilizes the photogeneration of reactive oxygen species (ROS) with high cytotoxicity to kill cancer cells, holding great promise for cancer treatment. Fractionated delivery of singlet oxygen (1O2) is a wise approach to relieving hypoxia, thus enhancing the therapeutic efficacy. In this paper, an anthracene functionalized semiconducting compound (DPPA) has been designed and synthesized. With irradiation, the compound is able to undergo efficient intersystem crossing (ISC) and non-radioactive decay for photodynamic/photothermal synergistic therapy. In addition, the anthracene module is able to capture and release 1O2 reversibly with or without irradiation. DPPA nanoparticles (NPs) obtained by nano-precipitation with DSPE-PEG exhibit considerable high phototoxicity on human kidney cancer cells (A498) and the half maximum inhibitory concentration (IC50) is 15.8 μg/mL. Furthermore, in vivo study demonstrates that complete tumor suppression was observed when the mice were administrated with DPPA NPs with the help of laser, compared with the control and dark group. The H&E analysis of the normal tissues (heart, liver, spleen, lung and kidney) indicate that such NPs cause no side effects, indicating the biosafety of DPPA NPs. The results provide a strategy to design heavy atom free photosensitizer for photothermal and fractionated PDT against kidney tumors.